Phenology, sex ratio, and spatial distribution among dioecious species of Trichilia (Meliaceae) - Morellato, LPC (Georg Thieme Verlag Kg, 2004)
The flowering, sex ratio, and spatial distribution of four dioecious species of Trichilia (Meliaceae) were studied in a semi-deciduous forest in southeastern Brazil. All reproductive trees (T. clausseni, T. pallida and T. catigua) with dbh greater than or equal to5 cm within a 1-ha plot were collected, sexed, mapped and, for individuals of each species, the distances to the nearest neighbour of the same and opposite sex were measured. For the shrub species T elegans (dbh <5 cm), all reproductive individuals were sampled randomly in 10 samples of 10 x 10 m. The reproductive phenology was observed at weekly to monthly intervals from May 1988 to January 1990. The species are strictly dioecious, did not present any sex-mixed trees or sex switching during the study, and sex ratio did not differ significantly from 1:1. The size distributions and the relative size variation were not significantly different. between sexes. There was no significant segregation or clumping between individuals of either sex and no fruit production without pollination. Onset of flowering and flowering peak were synchronous between male and female plants for all species studied. Flower synchrony was related to outcrossing and pollinator attraction rather than climatic factors.
Keywords: dioecy; Meliaceae; phenology; sex ratio; spatial distribution; Trichilia; tropical forest